The findings of the Industrial Policy Review Group - Cooney, Patrick J. (Statistical and Social Inquiry Society of Ireland, 1992)
Irish indigenous industry is my part of the overall picture and it is on my own particular experience in this sector that I will concentrate my views.
Symposium on the Findings of the Industrial Policy Review Group
Read before the Society, 26 March 1992
Keywords: Indigenous industry; Culliton report; 314.15